2007
DOI: 10.1016/j.juro.2006.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of TRAIL and its Receptors in Benign and Malignant Prostate Tissues

Abstract: Due to high TRAIL-R4 expression in all patient groups complementary gene therapy modalities might be needed to bypass potential TRAIL-R4 induced resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…In those studies, the presence of TRAIL decoy receptors on the surface clearly confirmed TRAIL resistance despite high levels of TRAIL death receptor expression. 27 Similar findings were reported by Hesry et al, who demonstrated that the TRAIL decoy receptor DcR2 was significantly more abundant in tumor cells than in nonneoplastic cells. 28 …”
Section: Mechanisms Of Apoptosis Resistance In Prostate Cancersupporting
confidence: 86%
“…In those studies, the presence of TRAIL decoy receptors on the surface clearly confirmed TRAIL resistance despite high levels of TRAIL death receptor expression. 27 Similar findings were reported by Hesry et al, who demonstrated that the TRAIL decoy receptor DcR2 was significantly more abundant in tumor cells than in nonneoplastic cells. 28 …”
Section: Mechanisms Of Apoptosis Resistance In Prostate Cancersupporting
confidence: 86%
“…Apopto sis is ini ti a ted when the se re cep tors are en ga ged by the ir li gands, that is, Fas li gand, TNF, and TRA -IL, res pec ti vely, which are eit her fre e in the cir cula ti on or bo und to the mem bra ne of cyto to xic ef fec tor cells. [17][18][19][20] Nuc le ar fac tor-kap pa B (NF-kB) ac ti va ti on, in ad di ti on to an in cre a se in the mRNA le vels of TNF-a, TNFR1, cas pa se 8, and cas pa se 3, has be en do cu men ted in rat mo dels of re nal obstruc ti on.…”
Section: Discussionmentioning
confidence: 99%
“…15 Analysis of prostate sections suggested that not only patients with benign prostate hyperplasia but also organ-confined prostate carcinoma or advanced prostate carcinoma displayed increased DcR2 receptor expression. 28 Moreover, elevated DcR2 expression levels in prostate cancer patients were linked to high Gleason scores, PSA recurrence and decreased survival. 42 Despite these studies, the relevance of TRAIL decoy receptor expression on TRAIL resistance or tumoricidal potential has not been directly investigated for the prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, high levels of DcR2 expression were not restricted only to the prostate cancer cell lines, but a similar correlation was also observed in patients with prostate carcinoma. 28 Thus, the current study was initiated to directly investigate the connection between high DcR2 expression and TRAIL resistance. To first rule out the possibility that inadequate TRAIL expression from the Ad5hTRAIL vector was the reason for the lack of any Ad5hTRAIL-mediated cytotoxicity in DU145 and LNCaP, we examined surface TRAIL levels by flow cytometry after Ad5hTRAIL infection.…”
Section: Trail Expression Following Ad5htrail Infection Does Not Overmentioning
confidence: 99%